Economic and Energy Analysis of Small Capacity Grid-connected Hybrid Photovoltaic-wind Systems in Mexico - Gallardo, Rafael Peña; Castro, Adalberto Ospino; Ramírez, Juan Segundo; Rodriguez, Aurelio Hernández; Angarita, Eliana Noriega; Maldonado, Yecid Muñoz (International Journal of Energy Economics and Policy, 2020)
The integration of renewable energies in the electric power system, as a solution to the growing demand for electricity in developing countries, has become a vital issue, such is the case of Mexico. The purpose of this work is the assessment of the economic and energy feasibility of a residential house grid-connected hybrid PV-Wind system, in Mexico. The hybrid PV-Wind system design is based on the existing renewable energy resources and considering a typical load profile. Also, an economic analysis is presented based on the two schemes approved for the sale of the surplus of the energy generated in Mexico: net billing and net metering. The results obtained demonstrate the viability and profitability of the proposed small-size system. However, the results corroborate that government incentives are crucial to making the proposed system more attractive and affordable for residential users. Keywords: Feasibility study, hybrid generation system, net billing, net metering, photovoltaic energy, wind energy. JEL Classifications: Q2, Q42, Q5 DOI: https://doi.org/10.32479/ijeep.8449